2021
DOI: 10.3390/ijms22094940
|View full text |Cite
|
Sign up to set email alerts
|

Activated ERK Signaling Is One of the Major Hub Signals Related to the Acquisition of Radiotherapy-Resistant MDA-MB-231 Breast Cancer Cells

Abstract: Breast cancer is one of the major causes of deaths due to cancer, especially in women. The crucial barrier for breast cancer treatment is resistance to radiation therapy, one of the important local regional therapies. We previously established and characterized radio-resistant MDA-MB-231 breast cancer cells (RT-R-MDA-MB-231 cells) that harbor a high expression of cancer stem cells (CSCs) and the EMT phenotype. In this study, we performed antibody array analysis to identify the hub signaling mechanism for the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 67 publications
0
12
0
Order By: Relevance
“…At the RNA level, overexpression of TPA diminished the expression of CDH1 and increased the expression of vimentin, fibronectin, and TGF-β1 ( 115 ). Circular RNA studies have shown that circNOLC1 ( 116 ) and circSCRIB ( 117 ) contribute to BC cell invasion and migration ability by reducing CDH1 and facilitating the tumorigenesis of breast cancer ( 118 ). Extracellular vesicles of insulin-like growth factor-1 (IGF-1), which is a crucial regulatory factor of mammary glands, promote the downregulation of CDH1 and upregulation of vimentin, N-cadherin, and MMP-9 in MDA-MB-231 breast cancer cells ( 119 ).…”
Section: Cadherins and Endocrine-related Cancersmentioning
confidence: 99%
“…At the RNA level, overexpression of TPA diminished the expression of CDH1 and increased the expression of vimentin, fibronectin, and TGF-β1 ( 115 ). Circular RNA studies have shown that circNOLC1 ( 116 ) and circSCRIB ( 117 ) contribute to BC cell invasion and migration ability by reducing CDH1 and facilitating the tumorigenesis of breast cancer ( 118 ). Extracellular vesicles of insulin-like growth factor-1 (IGF-1), which is a crucial regulatory factor of mammary glands, promote the downregulation of CDH1 and upregulation of vimentin, N-cadherin, and MMP-9 in MDA-MB-231 breast cancer cells ( 119 ).…”
Section: Cadherins and Endocrine-related Cancersmentioning
confidence: 99%
“…Most breast cancer patients receive radiotherapy after surgical resection; however, not all patients benefit equally because some have a locoregional relapse. The leading cause ( Table 2 ) of this relapse is radio resistance [ 63 ]. Radio-resistance is the adaptability of malignant cells or tissues to radiotherapy-induced damage and irradiation survival (IR) [ 64 , 65 ].…”
Section: Breast Cancermentioning
confidence: 99%
“…Radiation therapy can cause exhaustion and a red, sunburn-like rash where radiation is being delivered. Breast tissue may appear larger or stiffer as well [ 63 ]. These negative consequences might be debilitating.…”
Section: Breast Cancermentioning
confidence: 99%
“…In regard to breast cancer, radioresistant MDA-MB-231 breast cancer cells (RT-R-MDA-MB-231 cells) are malignant cells with a high metastatic activity, proliferation rate, and expression of CSC and EMT markers [ 99 ]. Paramanantham et al hypothesized the presence of an altered signal in those cells and set up an antibody array analysis on both radioresistant MDA-MB-231 and parental ones (p-MDA-MB-231) [ 100 ]. They found an upregulation of MAPK1, dual specificity protein kinase (CLK1), and fibroblast growth factor 22 (FGF22) and a downregulation of caspase-3 in RT-R-MDA-MB-231 cells.…”
Section: Protumoral Effects Of Csc-derived Evs On Non-csc Tumor Cellsmentioning
confidence: 99%
“…Molecular analysis revealed that ERK inhibition induced the cleavage of poly(ADP-ribose) polymerase 1 (PARP-1) and caspase-3 (apoptosis markers) in p-MDA-MB-231 cells and the activation of the apoptosis-inducing factor (AIF), which positively regulates cyclophilin A (CypA) protein (biomarker of necroptosis), in RT-R-MDA-MB-231 cells. In the latter, ERK inhibition markedly suppressed CSC and EMT markers [ 100 ]. Therefore, ERK signaling is strongly involved in the radioresistance of MDA-MB-231 breast cancer cells, suggesting that its targeting may offer a potential therapeutic strategy.…”
Section: Protumoral Effects Of Csc-derived Evs On Non-csc Tumor Cellsmentioning
confidence: 99%